Southwest Research-Extension Center: Another 50 Years of Progress (1957-2007) (Kansas Agricultural Experiment Station Research Reports, 2007)
The Garden City Branch Experiment Station was established in 1907. The mission was to serve the people of western Kansas by developing new knowledge and technology for agriculture. The current review will focus mainly on the second 50 years of the station’s history.
Keywords: 2007; history; crops; insects; irrigation; weed science; Extension; weather